Bilateral simultaneous achilles tendon ruptures. A case report and review of the literature - Price, A E; Evanski, P M; Waugh, T R (Clinical orthopaedics and related research, 1986)
Bilateral simultaneous Achilles tendon ruptures are rare, with only ten cases reported in the English literature. Our case is that of a 44-year-old woman, along with a review of the literature. Affected persons usually are on chronic steroid treatment and in the fifth to seventh decades of life. The patient may have concomitant systemic disease, and the injury occurs with relatively mild trauma. The goals of treatment are mainly preventative, i.e., cessation of steroids as soon as possible and protective bracing of the remaining intact Achilles tendon.